The Effect Of Good Corporate Governance On Firm Value With Financial Performance As An Intervening Variable - Kurniawan, Agung; Wahidahwati; Mildawati, Titik (Lead Journal of Economy and Administration, 2023)
This study aimed to find out either the direct or indirect effect of the board of directors, independent commissioners, and audit committees on firm value, with financial performance as the intervening variable. Furthermore, the population was State-Owned Enterprises that were listed on the Indonesia Stock Exchange (IDX) during 2018-2021. The data collection technique used purposive sampling, which used two criteria for the sample. In line with that, there were 20 companies as the samples which required to be observed. Moreover, the data analysis technique used Path analysis with SPSS. As the result, it concluded that (1) the Board of Directors did not affect the financial performance, (2) Independent Commissioners had a positive effect on financial performance, (3) Audit Committees did not affect the financial performance, (4) the Board of Directors had a positive effect on firm value, (5) Independent Commissioners did not affect firm value, (6) Audit Committees did not affect firm value, (7) Financial Performance had a positive effect on firm value, (8) Financial Performance could not mediate the Board of Directors on firm value, (9) Financial Performance could mediate Independent Commissioners on firm value, and (10) Financial Performance could mediate audit committee on firm value.